Assessment of the Left Ventricular Deformable Indices (Strain Components) in Different Echocardiography Systems - Karvandi, Mersedeh (International Journal of Cardiovascular Practice, 2018)
This Article provides simplified, easy-to-understand descriptions of the echocardiographic software used in conjunction with different echocardiography machines, such as those from Toshiba, Philips, GE, and Siemens, and explains how these sophisticated systems can best be used to exploit fully their ability to deliver more precise diagnoses and assist in treatment choice and follow-up. A variety of applications are covered, with presentation of algorithms and highlighting of tips and tricks. It will be of value for cardiologists, other interested clinicians, those pursuing fellowships in echocardiography, and sonographers; it will also be highly relevant for biomedical engineers, bio-mathematicians, computer scientists, and researchers in medical physics. There would be enormous clinical benefits of any non-invasive technique to estimate the true level of wall abnormal motions. Strain and strain rate are deformation measures. If different components of an object have different velocities, the object shape may be changed. In this article, we mentioned the left ventricular 2- dimensional strain in normal hearts for each different type of strain methods from 5 echocardiography machines and we have also introduced MATLAB software as an echocardiography desk.